Peranan Komunikasi Dalam Kinerja Organisasi - Ahmad Wahyudi; Muh. Abdul Aziz Nasuha; Margaretha Evi Yuliana (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
Communication is a vital element that influences all aspects of organizational life, from interpersonal relationships, teamwork, to interactions with external parties. In this context, research is conducted to understand how effective communication can enhance collaboration, efficiency, and creativity in the workplace. Through literature review and empirical studies, this article describes how communication errors can lead to barriers in task execution, create interpersonal tensions, and even impact the organization's reputation. Conversely, effective communication can foster a harmonious environment and support individual and organizational development. Good communication has a significant impact on overall organizational performance. Therefore, organizations need to recognize the importance of communication as a valuable tool to achieve strategic goals and cultivate a positive and productive work environment. By understanding and implementing the principles of effective communication, organizations can enhance productivity, collaboration, and creativity, which, in turn, will have a positive impact on the long-term success of the organization.